Utilización del método de electroquimioluminiscencia para la dosificación del Péptido C en pacientes diabéticos que acúden al Hospital IESS riobamba, durante el período febrero a julio 2015. - Guananga Vásquez, Lesly Marcela (2016)
This research has as its theme "USING THE METHOD electrochemiluminescence FOR DISPENSING Peptide C IN DIABETIC PATIENTS ATTENDING THE HOSPITAL IESS RIOBAMBA during the period February to July 2015," our formulation of the problem was: Does the method of electrochemiluminescence help in C-peptide dose in diabetic patients ?, in which propose intended use electrochemiluminescence method dosing C-peptide to aid in the diagnosis and management of diabetic patients, which specify patients with Type II diabetes are insulin by her determination of C-peptide, as hypothesis "using the method of electrochemiluminescence helped in the dosage of C-peptide in diabetic patients", for we consider the state of their anatomy, characteristics, effects, metabolism, secretion within the body in the patient with diabetes for further analysis of C-peptide, based on a suitable technique for there is an appropriate control to prevent diseases that can cause effect of high-risk patients who are hospitalized or after having discharged, in the present investigation applied the method, deductive and inductive, analytical, research is quasi-experimental and descriptive, bibliographical-documentary.